Neurofeedback games to enhance cognitive abilities - Lim, Wei Lun (2014)
In the usage of neurofeedback games to improve cognitive abilities, multitasking is one such ability that is experiencing increased attention, not only from researchers, but also from private corporations and the military. The ability to multitask is seen as a necessary skill in the performance of critical tasks, such as the piloting of an aircraft, which require aircraft personnel to monitor a number of status displays and communicate with air traffic control. Even in our daily lives, the ability to multitask can prove essential, such as when driving a vehicle while monitoring the GPS.